A systematic and comparative study of binary metal catalysts for carbon nanotube fabrication using CVD and laser evaporation - Jedrzejewska, Anna; Bachmatiuk, Alicja; Ibrahim, Imad; Srekova, Hana; Nganou, Collins; Schuechner, Frank; Borowiak-Palen, Ewa; Gemming, Thomas; Cuniberti, Gianaurelio (Giovanni); Buechner, Bernd; Ruemmeli, Mark H. (Fullerenes Nanotubes and Carbon Nanostructures, 2013)
Systematic studies to investigate binary catalysts combining the well-established standard transition metals Fe, Co and Ni with less used metals such as Al, Pb, Dy, Gd, Ga and Zn were explored in supported catalyst chemical vapor deposition. The findings show different carbon nanostructures can be obtained depending on the choice of catalyst mix. Comparative studies with Al as a co-catalyst with Fe or Co or Ni were explored in a laser evaporation reactor in both a pure nitrogen environment and a nitrogen environment with additional hydrogen present. The addition of hydrogen etches amorphous carbon leading to cleaner samples. In terms of the obtained carbon nanostructures, the variations among the different binary catalysts were the same for both synthesis routes investigated. © Taylor & Francis Group, LLC.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon nanotubes; Chemical vapor deposition; Laser ablation; Raman spectroscopy; Transmission electron microscopy